Please help ASAP. Thanks!

Best answer

Let’s simplify the function:

(x²(x²-2x-3))/(x²(x²-5x+6))=((x-3)(x+1))/((x-3)(x-2)), except when x=0;

(x+1)/(x-2) except when x-3=0, that is, when x=3. x-2=0, that is, x=2, means we will be dividing by zero.

So we can cancel out the factors x² and x-3, except when x=0 and 3, and we can evaluate the function, except when x=2. So the boxes must contain 0, 3 and 2.

- All categories
- Pre-Algebra Answers 12,316
- Algebra 1 Answers 25,282
- Algebra 2 Answers 10,443
- Geometry Answers 5,182
- Trigonometry Answers 2,640
- Calculus Answers 6,012
- Statistics Answers 3,020
- Word Problem Answers 10,111
- Other Math Topics 6,651

81,657 questions

85,896 answers

2,188 comments

69,324 users